Untouched Resources: The Potencies of Pondok Pesantren in Banyumas Regency - Lis Safitri; Ahmad Yusuf Prasetiawan (Ijtimā iyya Journal of Muslim Society Research, 2021)
Until today, pondok pesantren has special potential in various aspects to be developed, especially in economics. This study aims to classify the type and the potential of pondok pesantren in Banyumas regency. This study is a qualitative study with a descriptive-inferential method. The amount of 24 pondok pesantren has been learned. The data has been collected by observation, interview, and document review in 2019. The result showed that pondok pesantren in Banyumas Regency established in many types. Pondok pesantren salaf has higher economic potential than pondok pesantren khalafi and the convergence pesantren. Some of pondok pesantren salaf that need to be improved in entrepreneurship are Pondok Pesantren Al-Anwar Sumpiuh and Pondok Pesantren An-Najah. Pondok Pesantren Anwaarul Hidayah (Baturraden) and Pondok Pesantren An-Nur (Kedungbanteng) have agriculture potential. Pondok Pesantren An-Nur (Kedungbanteng) and Pondok Pesantren Mambaul Hikmah (Kembaran) need to be improved in fisheries business while Pondok Pesantren Al-Falah (Rawalo) and Nuururohman (Kemranjen) need to be improved in livestock. The other pesantren, Pondok Pesantren Roudhotut Tholibin (Kemranjen), Madrasah Wathoniyah Islamiyah (Kemranjen), and at-Taujieh have technological potential in computer and publishing.